2022
DOI: 10.1088/1748-605x/ac92b5
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-based assembled nanostructures that can direct cellular responses

Abstract: Natural originated materials have been well-studied over the past several decades owing to their higher biocompatibility compared to the traditional polymers. Peptides, consisting of amino acids, are among the most popular programable building blocks, which is becoming a growing interest in nanobiotechnology. Structures assembled using those biomimetic peptides allow the exploration of chemical sequences beyond those been routinely used in biology. In this Review, we discussed the most recent experimental disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 219 publications
(250 reference statements)
0
4
0
Order By: Relevance
“…Biomimetic strategies have been widely used in various types of research, such as tumor therapy ( He et al, 2022 ; Peng et al, 2022 ; Wu et al, 2022 ), vaccination ( Peng et al, 2022 ) and wound dress ( Mirhaj et al, 2022 ). And it has been reported that nanocarriers with bionic cell membranes were an effective and safe delivery system for osteosarcoma therapy ( Huang and Kiick, 2022 ). The shell of ZIF-8 has multiple functions to develop as a safe and effective platform for novel spore-based vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Biomimetic strategies have been widely used in various types of research, such as tumor therapy ( He et al, 2022 ; Peng et al, 2022 ; Wu et al, 2022 ), vaccination ( Peng et al, 2022 ) and wound dress ( Mirhaj et al, 2022 ). And it has been reported that nanocarriers with bionic cell membranes were an effective and safe delivery system for osteosarcoma therapy ( Huang and Kiick, 2022 ). The shell of ZIF-8 has multiple functions to develop as a safe and effective platform for novel spore-based vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…[124,126,127] The combination of two 1D assembly directions, along with further control over residue interactions, is able to successfully generate novel nanostructures such as nanotubes and single-layer nanoplates. [127][128][129][130] Although the high self-association tendency of β-sheet sequences hindered early efforts to study β-sheet-forming peptides, their strong but reversible self-association process of certain sequences has been harnessed to trigger aggregate formation in aqueous solutions and form hydrogels with high stability, strong mechanical properties, and self-healing [109] behavior. [118,123,131] Furthermore, the rigid structure of assembled β-sheet [120][121][122][123] peptides allows for the display of certain functional groups by selective mutation of key amino acid residues.…”
Section: Rlp-based Constructsmentioning
confidence: 99%
“…Both assembly processes successfully produce uniform nanofiber/nanoribbon structures [124,126,127] . The combination of two 1D assembly directions, along with further control over residue interactions, is able to successfully generate novel nanostructures such as nanotubes and single‐layer nanoplates [127–130] …”
Section: Constructs Comprising β‐Sheet Domainsmentioning
confidence: 99%
“…Although there are many advantages of NP nanocarriers, some limitations have motivated exploration of new NP formulations, for example, liposomes can show limited physical stability, thus causing burst release of cargo, and polymersomes can exhibit toxicity at high polymer concentrations . Therefore, research has continued on NPs that exhibit high biocompatibility, bioavailability, and stability, including those with their origin from peptides and proteins . Peptide-based NPs have specific benefits, such as engineerable self-assembly that can be tuned by the natural secondary structure of the protein fragments/peptides, a large variety of functional groups provided by different natural and non-natural amino acids, and easily synthesized sequences. With the ability to expand their functionality by conjugating peptide-based NPs with other molecules such as fatty acids or polysaccharides, they can also be utilized as biocatalysts or drug delivery carriers. …”
Section: Introductionmentioning
confidence: 99%